Electromobility in Forest Transport. Is It Feasible? Perceptions Regarding Implementation in the Chilean Industry - Larenas-Barra, Sebastián; Méndez-Dedes, Luis; Valdés-González, Héctor; Reyes-Bozo, Lorenzo; Sandoval-Yáñez, Claudia (Revista Científica, 2022)
This paper examines the different impressions and perspectives related to the implementation of electromobility in log transportation via trucks with a load capacity of up to 45 tons in the forestry sector of the eighth and sixteenth regions of Chile. The objective of this work is to establish the critical variables identified and perceived by key stakeholders of the forestry industry the correct implementation of high tonnage electric trucks. To this effect, a qualitative methodological study with a non-experimental design is proposed, which is based on semi-structured interviews conducted with stakeholders of the forestry sector of the study area. A convenience sample is employed, which was applied to four businessmen in the sector, three executives from the main forestry companies, and two truck distributor representatives. The data show that there is currently little knowledge due to the lack of specific projects and platforms for disseminating information that consider this technology in the field, but, on the contrary, they show a willingness to implement pilot plans aiming for the perceived economic sustainability of electromobility. A concentration of critical aspects is evidenced, which must be addressed in order to implement electromobility in forest transport, and which, given handling by public-private work, would enable the sector and the country to obtain the economic and environmental benefits of this technology.